Global Emerging Innovation Summit (GEIS-2021) - Dharam, Buddhi; Rajesh, Singh; Anita, Gehlot (Bentham Science Publishers, 2021)
This Global Emerging Innovation Summit (GEIS 2021) book summarizes the proceedings of the international summit held on April 9th and 10th, 2021. The meeting was organized by Lovely Professional University (LPU) and supported by ENEA - the National Agency for New Technologies, Energy and Sustainable Economic Development. GEIS-2021 is the most comprehensive conference focused on the diverse facets of the innovations in different technical domains. The goal of this conference is to bring together researchers from academia and industry as well as practitioners in allied fields to share their ideas and solutions related to issues and challenges that rely on the use of technology. The conference highlights the multifaceted nature of innovation in engineering and natural sciences. Attendees are given an opportunity to exchange new ideas to establish research relations to find global partners for future collaboration. Authors from academics, government agencies and industries, contributed several papers which truly make the conference a diverse and unique platform in the region for a productive and interdisciplinary dialogue. This volume features 59 contributions which were selected after review by the editors. Chapters cover emerging developments in a broad range sectors including aviation, transportation, pharmaceutical chemistry, medicine, life sciences, space science, electronics, security, artificial intelligence, communications, energy and much more. This compilation is a handy resource for readers who are seeking updates in the latest trends and innovative developments in technology and engineering.